Building trust in e-commerce from an Islamic perspective: A literature review - Muhammad, Marjan; Muhammad, Muhd. Rosydi; Suhaimi, Mohd Adam; Hussin, Husnayati; Mohamed Jalaldeen , Mohamed Razi; Abdullah, Kalthom (American Academy and Scholarly Research Center, 2013)
Studies indicate that trust has a significant impact on users’ acceptance of e-commerce. Discussion on the role of trust in e-commerce environment can be largely found in the literature; however, it scarcely looks at the issue from the Islamic perspective. As religion is one of the factors that helps to gain trust among Muslim internet users to conduct e-commerce, it is therefore pertinent to explore how to build online trust through an analysis of the essential requirements of e-commerce from the perspective of Islamic law of contract. Library research is employed by the means of investigating classical and contemporary literature to search for information on essential requirements underpinning e-commerce contract. Review of existing literature sheds light on some conditions related to offer and acceptance (form), buyer and seller (parties), and object and price (subject matter) of sale contracts concluded via online environment. An appraisal of these issues will justify the validity of e-commerce in Islamic law, thus enhancing the level of online trust among Muslim users.